P540 Early response as a prognostic factor for vedolizumab: A real-life experience from a single Italian tertiary centre. (16th January 2018) - Mezzina, N; Cassinotti, A; Carmagnola, S; Massari, A; Grillo, S; Landi, S; Maconi, G; Ardizzone, S
Abstract: Background: Vedolizumab (VDZ), a humanised monoclonal antibody targeting α 4 β 7-integrin, demonstrated efficacy in the treatment of ulcerative colitis (UC) and Crohn's disease (CD) in randomised controlled trials; however, data from real-world clinical practice are needed to confirm its effectiveness and safety, and to better identify patients who would benefit the most. Methods: In this retrospective cohort study, all consecutive patients starting VDZ at our centre between July 2016 and July 2017 and completing induction (Week 0/2/6) treatment were included. Clinical disease activity was assessed at baseline, at Week 14, 30, and at last infusion using Partial Mayo Score (PMS) for UC and Harvey Bradshaw Index (HBI) for CD. Clinical response was defined as a decrease ≥2 in PMS or ≥3 in HBI, whereas clinical remission as a HBI ≤4 or PMS ≤1. Rates of adverse events (AE) and surgery during therapy were also evaluated. Results: Seventy-five patients were included (45 UC, 30 CD), out of which 8 (11%) were naïve to anti-TNF therapy. At baseline, median PMS and HBI were 4 and 9, respectively. 65%, 40%, and 18% of patients received 14, 30, and 54 weeks of treatment, respectively. Overall, 27 patients had their treatment stopped (23 failures, 2 AEs, 2 other reasons), while 48 were still on treatment at the time of analysis. Median treatment duration was 30 weeks (IQR 16–44). At Week 14, 57% (43 of 75) responded to therapy, and 45% (34 of 75) were in clinical remission (40% UC vs. 53% CD, p = not significant). At Week 30, 37% (22 of 60) were in clinical remission (32% UC vs. 48% CD, p = not significant). Additionally, 18 patients (12 UC, 6 CD) received 1 year of therapy: 17 resulted still on treatment at last evaluation, and 72% (13 of 18) were in clinical remission. Most withdrawals of the treatment (74%) occurred before Week 30: the withdrawal rates were 13% at Week 14 and 33% at Week 30. Among patients who stopped the treatment, nine UC patients underwent colectomy and two CD underwent intestinal resection. Notably, patients who responded at Week 14 performed significantly better than patients with active disease at the same time, in terms of withdrawal rate (16% vs. 62%, p < 0.001) and remission at last follow-up (70% vs. 19%, p < 0.001). Conclusions: Our experience suggests that VDZ is effective and safe in IBD patients. Discontinuation rate was relatively high, especially in the early phases of treatment, but when an early clinical response was obtained, the vast majority of patients can be maintained clinical remission it in the medium–long term.